Fake peer reviews, fake identities, fake accounts, fake data: beware! - Teixeira da Silva, Jaime A. (AME Medical Journal, 2017)
Hopefully, for most scientists, science represents a path of exploration where the unknown/unexplored is the core challenge ahead. Sadly, in many respects, science has evolved from an exploratory model to a business model. It has become, in many instances, the verification tool for technologies, products and innovations that then establish corporate profits. Firstly, science evolved from being a relatively financially conflict-free zone of independent intellectual achievement where intellectual centers provided the necessary grants to complete basic research, to an important evaluation tool for so many products in our modern globalized societies (1). Secondly, scientists have implicitly evolved, or have had to evolve, from mere information seekers with a nerdy image in society, to important marketing agents of what they produce and discover. Pure science is becoming extinct because science is being treated as a marketing tool and driven by society’s demands. Information and intellect are copyrighted or patented, big data, peer review and open access are increasingly commercialized, and knowledge is no longer free to create, or divulge. When science is not driven by real academic and intellectual incentives, but instead by false incentives, this promotes an ambience of false discovery, or cheating. It also introduces business- and marketing-like values such as political correctness, and thus a considerably cold state of apathy, into academia. In the modern publishing era, metrics, which have zero academic value, but have tremendous marketing value for publishers, have come to dominate academics, and the altmetrics trend is not abating (2,3).